Morphological variability of acorns and its taxonomic significance in Quercus. from Turkey - Bakis, Y; Babaç, MT (Bangladesh Journal of Botany, 2015)
Morphological variations of acorn among and within the groups of Quercus species were studied. A total of 617 acorns belonging to 14 species representing all 3 sections of Quercus L. (Fagaceae) in Turkey were examined in this study. Specimens were collected from 47 different populations over both Anatolian and Thrace part of Turkey. Principal component analysis was used to analyze the morphological characteristics of acorns. Results obtained from this study demonstrate the use of morphological characters in differentiating the taxa of Quercus and Cerris sections studied. Another important finding is the introgression among the acorns of species within Quercus section DOI: http://dx.doi.org/10.3329/bjb.v43i3.21601 Bangladesh J. Bot. 43(3): 293-299, 2014 (December)